Menakar Progresivitas Hukum Wakaf dalam Pengembangan Wakaf Uang di Indonesia - Mansur Efendi (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2018)
This study explained the progressivity of waqf law in Indonesia, especially cash waqf development. The progressivity of waqf law is good enough to respond to global challenges or field needs. The progressivity of waqf law in Indonesia can be observed from the development of waqfs act regulations from pre-independence era until the post-reformation era. In cash waqf, there is fundamental law progressivity. It marked by act No. 44 year 2004 about waqf. Those act described new paradigm must be built on waqf management in Indonesia.  Furthermore, those act also gave a space for cash waqf as a part of waqf development in Indonesia. Another progressivity which appeared in those act is waqf treasure object. Act No. 44 year 2004 confirmed that waqf treasure object is not only immovable object,  as public understanding, but also applied on the movable object. Furthermore, the progressivity of waqf law has reached on waqf management and its institutional aspect. At least, this progressivity described collective awareness on the strategic role of waqf in Indonesias economics.